Awareness of Ebola: An Exotic Zoonotic Disease - NLPI Dharmayanti; I Sendow (WARTAZOA, Indonesian Bulletin of Animal and Veterinary Sciences, 2015)
Filovirus including Ebola and Marburg hemorrhagic fever is a zoonotic disease that characterised by immune suppression and systemic inflammatory response causing impairment of the vascular and immune systems. It is leading to multiorgan failures with mortality varies from 50-90% in human and primate. The Ebola virus is currently divided into five species, namely Zaire ebolavirus (ZEBOV), Sudan ebolavirus (SEBOV), Tai Forest ebolavirus, Reston ebolavirus (REBOV) and Bundibugyo ebolavirus. Geographical distribution of Ebola virus in the Afrotropics region is mainly in the rainforests of Central and West Africa, while REBOV was detected in the Philippines. Bats are suspected as reservoir host of the virus. Recently, Ebola cases had been reported in endemic areas in Africa and then distributed to other countries which was not endemic through human travellers. Ebola virus is also potentially used as a biological weapon, so Ebola virus becomes public health concern. This paper describes the characters of Ebola virus, its clinical signs, transmission and threat as an exotic disease in Indonesia. By understanding the disease, the emergence of Ebola virus in Indonesia can be anticipated quickly. Key words: Ebola virus, exotic, pathogen